Service to country : personnel policy and the transformation of Western militaries - Gilroy, Curtis L.; Williams, Cindy, 1947- (BCSIA studies in international security., 2006)
Motivated, able, and well-trained military personnel are essential to the success of any military, and personnel policies are crucial to getting and keeping qualified servicemen and women. The transformation of personnel policies is an important element of the broader transformation occurring in Western militaries. Across Europe and North America, nations are embracing plans to change military personnel policies to build future capabilities consistent with new strategic environments and with the demographic and societal realities of the future. For many nations, a key reform is to shift from a conscript military to a smaller, all-volunteer force. Other important reforms include expanding recruitment capacity, improving working conditions, revamping career paths, overhauling compensation systems and increasing military pay, modernizing pension plans, improving the quality of life for military members and their families, and improving the post-service prospects for those who serve. Service to Country explores the ongoing transformation of military personnel policies in Europe and North America, looking at causes as well as potential costs and benefits of personnel policy transformation. Contributors to the volume, from both Europe and North America, include experts from militaries, governments, universities, and think tanks; practitioners and scholars; economists, political scientists, sociologists, and a demographer. ContributorsJennifer Buck, Deborah Clay-Mendez, Sylvain Daffix, Chris Donnelly, Curtis Gilroy, Keith Hartley, Hannu Herranen, Bertel Heurlin, Jolyon Howorth, Gerhard Kummel, Juan Lopez Diaz, Karen McKenney, Mihaela Matei, Vincent Medina, Sebastian Negrusa, Cyr-Denis Nidier, Bernard Rostker, Robert St. Onge, Rickard Sandell, Peter Svec, Vaidotas Urbelis, Domenico Villani, John Warner, Cindy Williams, John D. Winkler